STUDI LITERATUR PENCIPTAAN TIMUR DEKAT KUNO - Imanuel Christian (Pengarah: Jurnal Teologi Kristen, 2019)
This article is an investigation to offer theological ideas about creation narrative based on Ancient Near East cultures. Through historical-cultural approach and using comparative study methods, this article will analyze creation narrative in Genesis 1:1-2:3 through the differences and similarities with Enuma Elish. According to the general assumption of similarities among cultural cults in the Fertile Crescent, this article will explore some theological ideas that the author of the book of Genesis would reveal. The result of the historical-cultural approach reveals that the author of Genesis had interest in to two large frameworks, namely the concept of creator and creation. Regarding the concept of creator, the things that are revealed is the affirmation of monotheism and the absence of theogony and nothingness of divine conflict. Then, regarding the concept of creation, creatio ex nihilo in Genesis 1:1-2:3, orderliness and perfection are the essence and character of creation.